SUTURE PLICATION OF PERFORATED DUODENAL ULCER - Muhammad, Gul; zeb, Aurang; Ahmad, Rashid; Sultan, Shahid; Ahmad, Sajjad (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: Seventy-five cases of perforated duodenal ulcer were managed by suture plication alone. Perforated acute ulcers have a better ultimate outlook in terms, of mortality and morbidity as compared with perforated chronic ulcers. It is suggested that chronic duodenal ulcer cases should have definitive surgery at the time of perforation or soon after the recovery, whereas acute ulcers should be primarily managed by suture plication alone. Where dyspeptic symptoms persist for more than 3 months in acute ulcers after suture plication definitive surgery must be done at the earliest opportunity.